An autonomic group communication protocol for distributed applications. (3rd April 2006) - Enokido, Tomoya; Takizawa, Makoto
We discuss a group protocol which supports applications with group communication service when QoS supported by networks or required by applications is changed. An autonomic group protocol is realised by cooperation of multiple autonomous agents. Each agent autonomously takes a class of each protocol function so as to support only and all QoS required. A group is composed of views for scalability. Each view is a subset of the agents where the agents autonomously take protocol classes consistent with each other. We make clear what combination of classes can be autonomously taken by agents in a view.